Cancer and aging: Reflections for elders- Expressive writing intervention: A pilot study. Issue 5 (June 2022) - Tutino, Rebecca C.; Saracino, Rebecca M.; Kelman, Judith; Schofield, Elizabeth A.; Roth, Andrew J.; Nelson, Christian J.
Abstract: Objectives: The Cancer and Aging: Reflections for Elders Expressive Writing Intervention (CARE-Express) was developed to enhance coping and minimize psychological distress in older adults with cancer. The aim of the current study is to evaluate the feasibility and initial efficacy of CARE-Express. Materials and Methods: Seventy-one distressed older adults (≥70) with cancer were assigned to CARE-Express ( n = 41) or the Enhanced Social Work Control (ESWC) arm ( n = 30). Participants completed five telephone sessions over seven weeks and were assessed on psychosocial variables at baseline, post-intervention, and four months post study enrollment. Feasibility was assessed by examining rates of eligibility, acceptance, retention, assessment, and fidelity. Initial efficacy was evaluated using standardized effect sizes. Results: Adequate rates of acceptance (29%), eligibility (66%), retention (90%), assessment (70% at post-intervention, 63% at four month follow-up), and fidelity (97%) were observed. At post-intervention, participants receiving CARE-Express reported less depression compared to ESWC (d = 0.69, p = 0.01) and lower demoralization (d = 0.50, p = 0.06). A small/moderate effect was demonstrated for increased total spirituality scores (d = 0.41, p = 0.07), meaning/peace (d = 0.32, p = 0.20) and faith (d = 0.35, p = 0.07). The CARE-Express group reported greater reductions in behavioral disengagement (d = 0.44, p = 0.06), while ESWC demonstrated a small effect for active coping (d = 0.21, p = 0.31). At four months, differential effects of CARE-Express had attenuated, though small/moderate, effects in favor of CARE-Express remained. Conclusion: Results support the feasibility of CARE-Express and its potential positive impact on psychological well-being. Trial registration: Registered at the US National Institutes of Health (ClinicalTrials.gov ) #NCT00984321 on September 25, 2009.